Penanggulangan Masalah Pedagang Kaki Lima di Kota Manado Pada Perspektif PKL - Sundalangi, Frankie (JBE (Journal of Business and Economics), 2009)
The city of Manado with a population of 420,351 is accoupied by 4,046 street hawkers (street vendors). Some believe street hawkers have helped the city goverment in solving unemployment problem. For buyers, shopping is convenient because it relatively easy to find what they want. They can also buy their shopping goods at a relatively cheaper price. For this reason, steet hawkers are often called asset of the city, the heroes, and many other names. On the other hand, Goverenment and society consider them as trouble makers.traffic jams, dirty roads and streets, choas, are among the problems addressed to them. For this reason, thies topic was chossen: a study on how to solve the problem of street hawkers in the city of Manado. The method used in this study is descriptive survey. The researcher has chosen a sample of 343 out of 4,036 street hawkers and how they do business in the city of Manado. The researcher has also chosen 149 city officers, 13 street policemen, and 44 pedestrians. All samples are selected randomly. There are two questions givin to all respondent: What is the main problem of the existence of street hawkers in the city of Manado? What is the solition to the above problem? Answers to both questions were then analyzed and calclated. The results of this survey are reported as findings to this study. These findings are as follows: the problem of the street hawkers: From the viewpoint of street hawkers, the main problem is that goverment has located them in a non-strategic area, a too quiet location with less buyers and passersby. From the viewpoint of city officers, street policemen, and pedestrians, the mere existence of street hawkers have created traffic jams and dirty city. The sulation of the problem of street hawkers: Majority of the street hawkers have requested to move to a better location, besically where there are many passersby. They also request city officers to change the route of public transpotation to pass certain locations where they are located. Majority of the group of respondents which consist of city officers, street security, and pedestrians opt for relations of street hawkers. Based on these findings, the researcher suggests to all decision makers involved to relocate street hawkers to a more proper place, and to rule them accordingly.